Knowledge and opinions about banking supervision: Evidence from a survey of Dutch households - van der Cruijsen, Carin; de Haan, Jakob; Jansen, David-Jan; Mosch, Robert (Journal of Financial Stability, 2013)
What does the general public know about banking supervision? What objectives does the public think bank supervisors should pursue? We investigate these issues using a survey among Dutch households. First, we find that the public's knowledge about banking supervision is far from perfect. We also find that respondents often expect more from supervisors than they can realistically achieve. Finally, our findings suggest that better-informed people have more realistic views on banking supervision. Realistic views on banking supervision lead to more prudent financial behavior, which, in turn, contributes to financial stability. Therefore, the communication policies of banking supervisors should aim to improve the public's knowledge about banking supervision.